Differentiating Local and Global Vibration Modes of Heritage Masonry Buildings through the Spatial Correlation of Modal Displacements. Issue 4 (3rd April 2022) - Rainieri, C.; Fabbrocino, G.; Brigante, D.
ABSTRACT: The effective differentiation between global and local modes plays a fundamental role in the selection and application of the most appropriate seismic analysis procedures. This is particularly relevant in the case of historical heritage structures and ensembles of buildings in old city centres: due to the complexity of the structural scheme, the stratification of interventions, and the irregularity of the structural configuration with the absence of seismic details, several local modes frequently characterize the dynamic response of those structures. Distinguishing local and global modes might be challenging even from the experimental point of view in the presence of few measured degrees of freedom. Nevertheless, an accurate analysis of local modes can support the identification of macro-elements and the selection of the most appropriate analysis procedure. The present paper illustrates an original approach addressing the differentiation between global and local modes through the spatial correlation of modal displacements. The proposed approach can be either automated and integrated into software for structural analysis or applied in the context of an experimental campaign, and its application to simulated case studies is discussed.